A miniaturized and high-gain antipodal Vivaldi antennas using directors - Al Gburi, Ahmed Jamal Abdullah; Ibrahim, Islam M.; Elsherbini, Moataz M.; AbdelKader, Hala M.; Ahmed, Mohamed Ismail (Electromagnetics Academy, 2024)
In this paper, a miniaturized millimeter-wave (mm-wave) antipodal Vivaldi antenna (AVA) is proposed. The AVA antenna structure is modeled using MWSCST2022 optimization tools. The AVA exhibits good impedance matching, high gain, and a small optimum size of 5 × 2.5 × 1.5 mm3, fabricated on an FR-4 substrate. An array of square and circular director units is modeled and loaded at the front and back of the AVA antenna. The spacing between directors is studied and positioned at a tuned distance from the antenna for gain improvements and optimum radiation parameters. The AVA has an operating spectrum from 58 GHz up to 62 GHz. The finalized AVA, along with directors, obtained a high gain of 12.9 dBi with directors, while the AVA achieved 9.22 dBi without directors. The proposed antenna model is simulated and measured for short-range communications and imaging. The results of the modeling techniques and measurements agree well with each other.